i-LEPRA: POTENSI MIKROSFER KOMBINASI FUKOIDAN DAN MIP SPESIFIK ANTIGEN ML0405 SEBAGAI INOVASI VAKSIN Mycobacterium leprae - Satyarsa, Agung Bagus Sista; Iqra, Haikal Hamas Putra; Pratama, Gede Made Cahya Trisna; Sudarsa, Prima; Rusyati, Luh Made Mas; Swastika, I Made (Essential: Essence of Scientific Medical Journal, 2019)
Introduction: Leprosy is a chronic infectious disease that caused by M. leprae, which has predilections to skin and peripheral nerve. WHO predicts that there are aproximately 12 million people world-wide suffered from leprosy, and almost 80% come from tropical countries. Nowadays, leprosy becomes main problem from medical and social views. Prevention of leprosy appears to be a promising strategy in order to eradicate leprosy. In this case, vaccination is the most suitable strategy. Unfortunately, these day vaccines only have protective efficacy less than 70%. More proactive strategies are necessary in order to develop specific vaccine which enhance immune system against M. leprae. Method: This study used literature reviews, using database from www.pubmed.com and scholar.google.com that met the inclusion criteria. From 108 journals, we obtained 78 journals. Discussion: MIP is well-known to be an effective vaccine that has been through clinical trial test phase III. MIP has shown some cross-reactive component antigen which can enhance T cell response to M. leprae. Furthermore, the combination with fucoidan microsphere and antigen specific ML0405 which has predilection for machrophage and as immunomodulator, can maximize the ability of MIP as vaccine to prevent leprosy. Product of combination MIP specific antigen ML0405 and fucoidan microsphere called i-LEPRA. Conclusion: However, further research is needed to identify i-LEPRA efficacy and efficiency. Therefore, i-LEPRA is expected to be effective and efficient as an innovative vaccine against M. leprae in the future.